Smokeless tobacco: A major public health problem in the SEA region: A review - CecilyS Ray; PrakashC Gupta; DhirendraN Sinha; PoonamK Singh (2011)
Smokeless tobacco use is on the upswing in some parts of the world, including parts of SEAR. It is therefore important to monitor this problem and understand the possible consequences on public health. Material for this review was obtained from documents and data of the World Health Organization, co-authors, colleagues, and searches on key words in PubMed and on Google. Smokeless tobacco use in SEAR, as betel quid with tobacco, declined with increased marketing of cigarettes from the early twentieth century. Smokeless tobacco use began to increase in the 1970s in South Asia, with the marketing of new products made from areca nut and tobacco and convenient packaging. As a consequence, oral precancerous conditions and cancer incidence in young adults have increased significantly. Thailand's successful policies in reducing betel quid use through school health education from the 1920s and in preventing imports of smokeless tobacco products from 1992 are worth emulating by many SEAR countries. India, the largest manufacturing country of smokeless tobacco in the Region, is considering ways to regulate its production. Best practices require the simultaneous control of smokeless and smoking forms of tobacco. Governments in SEAR would do well to adopt strong measures now to control this problem.